2021
DOI: 10.1038/s41598-021-95529-y
|View full text |Cite
|
Sign up to set email alerts
|

The immune status, oxidative and epigenetic changes in tissues of turkeys fed diets with different ratios of arginine and lysine

Abstract: In the present experiment, it was assumed that the appropriate dietary ratio of arginine (Arg) to lysine (Lys) can improve the immune status and growth performance of turkeys. The aim of this study was to evaluate the effects of two inclusion rates of Arg relative to Lys in turkey diets with Lys content consistent with National Research Council (NRC) recommendations or 10% higher on the immune status of birds and indicators of protein and DNA damage due to oxidation, nitration or epigenetic changes. Another go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
1
1
Order By: Relevance
“…Therefore, they do not contribute to chronic stimulation that reduces the efficiency of the immune system. Analysis of the immune and redox status of the small intestinal wall of birds do not corroborate the results of our previous study [ 40 ] where turkeys were fed diets with different Arg:Lys ratios relative to Met. In the cited study, no significant interactions were found between different dietary proportions of Arg and Lys vs. the immune response and the antioxidant status in the intestinal wall and blood of turkeys.…”
Section: Discussioncontrasting
confidence: 90%
“…Therefore, they do not contribute to chronic stimulation that reduces the efficiency of the immune system. Analysis of the immune and redox status of the small intestinal wall of birds do not corroborate the results of our previous study [ 40 ] where turkeys were fed diets with different Arg:Lys ratios relative to Met. In the cited study, no significant interactions were found between different dietary proportions of Arg and Lys vs. the immune response and the antioxidant status in the intestinal wall and blood of turkeys.…”
Section: Discussioncontrasting
confidence: 90%
“…Доказано, что введение аргинина способствует снижению уровней IL-6 и моноцитарного хемоаттрактанта. Установлено, что регуляция доступности аргинина является потенциальным механизмом, контролирующим продукцию NO, активацию iNOS и аргиназы, отражающим тип воспалительного ответа в условиях патологического состояния [18]. Наряду с этим, аргинин служит предшественником многочисленных биологически активных соединений таких как, оксида азота, орнитина, пролина и полиаминов, креатина и, следовательно, фосфокреатина и агматина, которые так или иначе участвуют в реализации иммунных механизмов.…”
Section: Victim Animalsunclassified
“…DL-methionine contained 990 g methionine/kg (MetAMINO ® ; Evonik Degussa GmbH, Essen, Germany). 1 Source: Ognik et al [ 17 ]. 2 L Low A Low , diet with low Lys and low Arg levels; L Low A High , diet with low Lys and high Arg levels; L High A Low , diet with high Lys and low Arg levels; L High A High , diet with high Lys and high Arg levels.…”
Section: Tablementioning
confidence: 99%